Mas você não tem cara de autista: relato autobiográfico, diagnóstico tardio e campo dêitico - Castro, Lorena Gomes Freitas de (2023)
This work proposes a displacement of the neurotypical perspective both in comprehension and in academic writing, bringing to light reports of autistic people after late diagnosis, in favor of neurodivergent subjectivity (BENEDETTO, 2020; ORTEGA, 2008). Our research is aligned with a socio-cognitive-interactional perspective of the functionalist language of the studies, since it presupposes the language in interaction, in functioning and as a result of principles that can exert significant changes in the effects of meaning, namely, the social, cognitive, cultural, identity contexts, among others. From the theoretical scope of Textual Linguistics in contemporary times (KOCH, 2009; MARCUSCHI, 2012; CUSTÓDIO FILHO, 2009; CAVALCANTE; CUSTÓDIO FILHO; BRITO, 2014; CAPISTRANO JÚNIOR; LINS; ELIAS, 2017; LIMA; CASTRO, 2021), autobiographical reports have been analyzed of autistic people who, coming from late diagnoses (between adolescence and adulthood), can constitute discursive tools to combat prejudice and oppression, to promote the recognition of neurodiversity and the development of these identities (BENEDETTO, 2020; LACERDA, 2017; DONVAN; ZUCKER; 2017; GRANDIN; PANEK, 2021; BERNIER; DAWSON; NIGG, 2021). To do so, the phenomenon of referencing through the (re)elaboration of discourse objects is discussed (MONDADA; DUBOIS, 2013), which point to the referential construction of atypical (id)entities, in addition to a before-after continuum in the context of this diagnosis. This means that these (id)entities are (re)constructed, indicating places of neurodissidence and considering, in this process, all there was before as the absence of this diagnosis and that came after as the experience of access to the late diagnosis of ASD. The sample contains materials that were collected exclusively through a virtual questionnaire (google forms). Our interest in the absence of greater knowledge about this topic has been justified. For this, we have to analyze, as a general goal, the way in which the (re)construction of atypical (id)entities occurs from autobiographical reports of autistic adults with late diagnosis, and how specifically: (1) to discuss the contextual social markers of the participants through data obtained through a digital form; (2) to identify and describe discourse objects in reports, taking into account neurodiversity and (3) to analyze autobiographical reports written from the use of referential processes and, above all, those of the deictic field. In addition to these aims, we defend the hypothesis that through the referential analysis of these reports, we confirm dissident traits, deconstructing the ableism questioning “but you don't look like an autist!”. We reiterate, therefore, that neurodissident reports of autistic people with late diagnosis provide the (re)cognition of the neurodiversity of these (id)entities. Regarding the atypical final grades, these ideas are also supported by the scientific recognition of my own diagnosis, of my before/after, identifying the structural ableism. We also point out the cathartic power of the reports and the importance of a bellhookian love ethic in favor of anti-ableist literacy.